Efeitos da Anredera cordifolia em modelo de cicatrização: estudo bibliográfico e experimental - Heisler, Elisa Vanessa (2024)
Introduction: Wound healing is one of the fundamental factors for the survival of human beings and the maintenance of their quality of life. Many plants have been and are used by popular medicine for the prevention and healing of skin lesions, including Anredera cordifolia. Objective: compile scientific productions and evaluate the effect of A. cordifolia extract on the healing process of skin lesions, in in vitro experimental models, with commercial human cells (HFF-1-fibroblasts) cultivated in a normoglycemic and hyperglycemic environment. Methodology: the work was developed based on two protocols: literature reviews and in vitro experimental study. These protocols were organized into three productions (one book chapter and two articles). In the book chapter, a narrative review was developed on national scientific trends regarding the plant Anredera cordifolia. In article 1, an integrative review was carried out on the biological effects of the A. cordifolia plant. In article 2, the effect of the ethanolic extract of A. cordifolia in an in vitro healing model was evaluated: a) the ethanolic extract was prepared and chemically characterized; b) non-cellular assays were carried out to evaluate the antioxidant and genoprotective capacity of the extract; c) using the HFF-1 strain, pharmacological curves were performed to define the concentration of use, then the intact or scratched cells (in vitro injury) were exposed to a normoglycemic or hyperglycemic environment and treated with the extract of A. cordifolia at the concentration of 1 µg/mL for 6 and 24 hours to evaluate markers of cytotoxicity, cell proliferation, oxidative markers and those associated with collagen synthesis and degradation. Results: Protocol 1, Brazilian research on the species is focused on the nutritional importance and agronomic management of the plant, with the lack of national studies interested in medicinal properties being the main gap in knowledge. The review on international bases, on its therapeutic effects, allowed us to observe that they are described: healing action, antibacterial, analgesic, antihypertensive, antihyperuricemic, antihyperlipidemic and cytotoxic activity. And in the treatment of renal failure, anti-obesity effect, antihyperglycemic effect, anti-cataratogenic effect, effects on learning, memory and fertility. Regarding protocol 2, the results demonstrate that the main bioactive molecule is phytol. A. cordifolia, both in normoglycemic and hyperglycemic environments, showed a genoprotective effect, promoted cell migration and proliferation, and induced a significant increase in the extracellular expression of collagen and related genes. Conclusion: The results point to antioxidant, genoprotective, pro-migratory and proliferative action in fibroblasts, anti-apoptotic, and phytogenomic effect on collagen metabolism in both normoglycemic and hyperglycemic lesions promoted by A. cordifolia. Which may explain the effectiveness of this medicinal plant in healing skin injuries. For nursing, the study is relevant and innovative, revealing important evidence about the biological effects and mechanism of action of the species, bringing popular knowledge closer to scientific knowledge. The results contribute important inferences that in the future may lead to the development of new herbal medicines, safe to use, encompassing greater access to medicines.